13 bankers : the Wall Street takeover and the next financial meltdown - Johnson, Simon, 1963-; Kwak, James (New York : Vintage Books, 2011)
Provides historical context for the 2008 financial crisis and proposes a radical solution, the megabanks deemed "too big to fail" must be made smaller.--
Introduction: 13 bankers -- Thomas Jefferson and the financial aristocracy -- Other people's oligarchs -- Wall Street rising : 1980- -- "Greed is good" : the takeover -- The best deal ever -- Too big to fail -- The American oligarchy : six banks.
Originally published: New York : Pantheon Books, c2010.
"With a new epilogue"--Cover.
Includes bibliographical references (pages [233]-290) and index.
Keywords: Banks and banking -- United States; Bank failures -- United States; Finance -- United States; Financial crises -- United States; Economics